Aspectos influenciadores de compras planejadas e não planejadas: uma análise com cluster e regressão logística - Santa Catarina, Graciele Maria Frois (2009)
Knowing the consumer and their attitudes at the completion of purchases is a behavior that has been studied for several decades. Based on the theory of consumer behavior this study is to spend one more contribution to academia and industry, to present the factors that influence young people to the habit of doing or not planning ahead to situations of purchase. Thus the problem of research proposed in this study was: "What are the factors that influence the act of performing and non-planned purchases planned?". For this was a descriptive study of the quantitative type, involving a survey of field of 600 respondents, a stratified sample covering the proportion of graduate students from four institutions of higher education. Was extracted from the literature review some factors that could be linked to the fact that the purchases are made in a planned or not and, therefore, could be investigated. Bearing in mind that each factor was chosen consisting of many variables realized the need to reduce the initial set of variables, but without compromising the original meaning of each factor and, therefore, appealed to the statistical technique of cluster analysis. For a better understanding of the phenomenon it was studied by logistic regression analysis applied to other variables of the previous technique, there are aspects that are related to the increased likelihood that the purchases are planned and implemented in a Nor -planned. Thus, it was found that self-esteem and age tend to increase the chance of occurring and that the purchases planned income, materialism and compulsive buying behavior increases the likelihood of non-planned purchases occur. Furthermore, no relationship was found between any of the family structure and social factors to the act of planning or not purchasing the university. How the results can not be generalized, taking into view that was conducted among a specific audience, they become further research to better understanding and deeper in this area of study.